1997
DOI: 10.1113/jphysiol.1997.sp022051
|View full text |Cite
|
Sign up to set email alerts
|

Human body‐segment tilts induced by galvanic stimulation: a vestibularly driven balance protection mechanism.

Abstract: 1. We have studied the effects of changes in posture on the motor response to galvanic vestibular stimulation (GVS). The purpose of the experiments was to investigate whether the function of the GVS-evoked response is to stabilize the body or the head in space. Subjects faced forwards with eyes closed standing with various stance widths and sitting. In all cases the GVS-evoked response consisted of a sway of the body towards the anodal ear. 2. In the first set of experiments the response was measured from chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
205
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(228 citation statements)
references
References 17 publications
16
205
0
2
Order By: Relevance
“…Previous authors observed biphasic CoP responses using longduration GVS pulses (Ͼ1-s stimuli), with the larger, second response directed toward the anode (8,24). The polarity and timing of the first and second CoP components observed by these authors correspond to the characteristics of the second and third CoP components observed here.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Previous authors observed biphasic CoP responses using longduration GVS pulses (Ͼ1-s stimuli), with the larger, second response directed toward the anode (8,24). The polarity and timing of the first and second CoP components observed by these authors correspond to the characteristics of the second and third CoP components observed here.…”
Section: Discussionsupporting
confidence: 60%
“…Such stimuli have been thought to evoke motor responses with minimal or no balance response, but it remains to be determined whether such brief GVS pulses specifically evoke vestibulomotor responses or if they evoke a concommittant balance response. The primary aim of the present study was to quantify the muscle and balance responses associated with brief 20-ms GVS pulses.Muscle and whole body responses elicited by GVS during quiet standing have been mostly described, regardless of the body and CoP position (8,38,39). One notable exception, however, is a study by Marsden et al (23), who showed that asymmetric stance alters vestibular-evoked postural responses.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…There is literature to suggest that the SL response may not be consistent or reliable when the vestibular stimulus is below 2 mA (Ali, Rowen, & Iles, 2003; Fitzpatrick et al., 1994). Additionally, the quality of the reflexes may have been compromised with head orientation, as the reflexes are obtainable [as evidenced by the results of our study and other experiments (Dakin, Son, Inglis, & Blouin, 2007; Day et al., 1997; Forbes et al., 2016; Nashner & Wolfson, 1974)], yet not as prominent in the soleus muscle with the head facing forward (Fitzpatrick et al., 1994). Most studies examining vestibular reflexes have subjects stand with their head facing over the shoulder (Britton et al., 1993; Fitzpatrick et al., 1994; Lund & Broberg, 1983; Nashner & Wolfson, 1974; Welgampola & Colebatch, 2001), however, we opted to test the reflexes with head forward as we have shown in a previous experiment that depressing the cerebellar vermis with cTBS can result in a modulation in the postural sway direction, such that it is no longer intra‐aural with the head facing over the shoulder (Lam et al., 2016).…”
Section: Discussionmentioning
confidence: 99%